Clinicohematological and molecular analysis of hemoglobin D syndrome and unknown variants in the hemoglobinopathy spectrum of Sindh, Pakistan - Sunila Tashfeen; Ikram Din Ujjan; Hina Shaikh; Muhammad Arif Sadiq; Feriha Fatima Khidri; Ali Raza Rajput; Ali Muhammad Waryah (PLoS ONE, 2025)
Objectives Hemoglobinopathies are prevalent monogenic disorders resulting from genetic abnormalities in globin genes, significantly impacting health. β-thalassemia is particularly common in Pakistan, but data on other hemoglobin variants remain limited. This study aimed to investigate HbD syndrome, identify unknown variants, and examine the clinicohematological and molecular profiles of hemoglobinopathies in Sindh, Pakistan. Methods A prospective cross-sectional study was conducted from January 2021 to January 2023 at Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro, Pakistan. Blood samples were collected from across Sindh, Pakistan and analyzed for hemoglobinopathies using hematological tests (CBC, peripheral blood smear), cation exchange high-performance liquid chromatography (CE-HPLC) and molecular analysis to confirm HbD and identify rare variants. Data were analyzed using SPSS v. 27. Results Out of 4783 chromatograms analyzed, 1563 (32.7%) were diagnosed with hemoglobinopathies. The most common conditions included β-thalassemia (81.4%), hemoglobin (Hb) variants (11.2%), and hereditary persistence of fetal hemoglobin (7.4%). HbD was found in 2.1% of cases, with HbD syndromes being the most prevalent among Hb variants (56.6%). Sickle cell disorders followed with a frequency of 32%, and HbQ, HbE, and HbC were less common. Molecular analysis confirmed the HbD Punjab variant and identified an additional four mutations, i.e., one rare β-thalassemia mutation and three Hb variants including Hb Hinsdale, Hb Renert and Hb Takasago. Conclusion Hb D Punjab is the most prevalent hemoglobin variant in Sindh, Pakistan, followed by HbS and HbQ. Molecular analysis is essential for accurate diagnosis and identifying rare variants. Integrating HbD detection into screening programmes and genetic counselling can help prevent hemoglobinopathies. (S1 Abstract Graphic).